Chemisorption and physisorption of polymer nanocomposite membranes - Murtala, Namakka; Md. Rezaur, Rahman; Norazzlina, M.Sa'don; Muhammad Khusairy, Bakri; Ain Zaienah, Sueraya (Woodhead Publishing is an imprint of Elsevier, 2025)
Polymer membrane technology is an emerging technology for purification and separation processes. Although different types of polymeric membranes have been developed for water treatment, challenges such as fouling, hydrophobicity, and weak mechanical strength still need to be resolved. Many researchers are concentrating on creating polymer nanocomposites by blending various nanomaterials with polymer matrices to enhance the characteristics of the original polymer matrices. The success of these membranes hinges on the complex interactions occurring at the interface, influenced by both chemisorption and physisorption. This chapter discusses the concepts of physisorption and chemisorption. It examines the mechanism of these concepts on various polymer nanocomposite material surfaces and the methods to enhance the interaction between polymers and nanoparticles to improve key performance metrics such as permeability, selectivity, and resistance to fouling.